2019
DOI: 10.3390/designs3020023
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Usability of Homecare Applications for Older Adults: A Case Study

Abstract: As the world’s population is ageing, the field dealing with technology adoption by seniors has made headway in the scientific community. Recent technological advances have enabled the development of intelligent homecare systems that support seniors’ independent living and allow monitoring of their health status. However, despite the amount of research to understand the requirements of systems designed for the elderly, there are still unresolved usability issues that often prevent seniors from enjoying the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…If an application was mentioned in several studies, only the original evaluation report was included. As Panagopoulos et al (34;35) evaluated, redesigned, and re-evaluated their application, both evaluation studies were included in the analysis. See Table 1 for an overview of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…If an application was mentioned in several studies, only the original evaluation report was included. As Panagopoulos et al (34;35) evaluated, redesigned, and re-evaluated their application, both evaluation studies were included in the analysis. See Table 1 for an overview of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, in terms of sample size, duration and type, the evaluations vary widely. Four studies (18;34;35;37) used 1-day usability workshops, whereas another study (41) observed the usage of an application for more than 6 months. All applications were tested without randomized control groups or pre-post comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years the health care and assisted living has gained much attention among researchers. In a case study, Panagopoulos et al [ 2 ] presented a usability assessment of “Heart Around”, an integrated homecare solution incorporating communication functionalities, as well as health monitoring and emergency response features. Loukatos et al [ 3 ] investigated educationally fruitful speech-based methods to assist people with special needs to care for potted plants.…”
Section: Introductionmentioning
confidence: 99%